India - Chatterjee, Manini; Roy, Anita (New York : Dorling Kindersley, 2002)
Here is a compelling and visually stunning guide to the rich diversity of life in India. Photographs show fascinating customs and rituals together with exquisite artworks, artifacts, and temples--offering a unique "eyewitness" of the intriguing nation.
Diverse land - First great civilizations -- Land of the Buddha -- Two ancient empires -- Conflicts in the north -- Kingdoms of the south -- Great Mughals -- Taj Mahal -- Arrival of the Europeans -- British Raj -- Struggle for freedom -- Free India -- Life in the village -- Big cities -- Art & sculpture -- Traditional craftwork -- Fabrics & weaves -- Jewelry -- Literary tradition -- Music -- Classical dance -- Cinema & theater -- Mouthwatering cuisine -- Animal kingdom -- Science & technology -- Medicine & healing -- Religion & beliefs -- Rites & rituals -- Festivals.
Includes index.
99370
Keywords: India -- History; India -- Civilization; India -- Social life and customs; India